Theory of planned behavior and Instagram influencer attitudes: effects on Generation Z fashion purchase intention - Ramadani, Nadia; Dwita, Vidyarini (Universitas Negeri Padang, 2025)
This study aims to analyze the influence of Theory of Planned Behaviour with Attitude Toward Influencers as Mediation on Purchase Intention of Fashion Products on Instagram in Gen Z. The sampling technique used purposive sampling. The research participants totaled 190 respondents who were selected as samples. Analysis using PLS 4.1 software shows that perceived trust, subjective norms, perceived behavioral control, and attitudes toward the influencer, significantly affect attitudes toward the influencer and purchase intention. However, perceived trust does not significantly affect purchase intention. Attitudes toward the influencer mediate the relationship between perceived trust, subjective norms, perceived behavioral control and purchase intention.